A new sol–gel route towards Nd3+-doped SiO2–LaF3 glass-ceramics for photonic applications. Issue 9 (27th November 2020) - Cruz, María Eugenia; Durán, Alicia; Balda, Rolindes; Fernández, Joaquín; Mather, Glenn C.; Castro, Yolanda
Abstract : Optical luminescence emission of 0.9Nd 3+ –80SiO2 –LaF3 glass ceramic. Abstract : Glass-ceramic materials with composition 0.9Nd 3+ –80SiO2 –20LaF3 were successfully obtained and further heat-treated at 450 °C for 6 h. Stable and homogeneous LaF3 nanoparticle suspensions with and without Nd 3+ were first prepared by a chemical route, incorporating polyvinylpyrrolidone (PVP) as dispersant. The suspensions were then concentrated and characterised by XRD, HRTEM and zeta potential, confirming that LaF3 crystallises as the only phase, with particle size around 16 nm. The suspensions were incorporated in a silica sol to obtain a 0.9Nd 3+ –20LaF3 –80SiO2 particulate sol, xerogel and glass-ceramic. HRTEM confirmed the homogeneous incorporation of the doped nanocrystals into the SiO2 matrix without modification of the nanoparticle structure. Rietveld refinement was used to determine the crystallinity and quantity of LaF3 nanoparticles present in the glass-ceramic after treatment of the particulate sol at 450 °C for 6 h. Luminescence measurements of near infrared Nd 3+ ion emissions in the lanthanum fluoride nanoparticles and SiO2 –LaF3 glass-ceramic showed well-structured emission spectra with lifetimes similar to those of theoretical Nd +3 in LaF3 crystals.